THE ISLAM FACTOR IN THE POSITIONING OF RUSSIA’S REGIONS - Mikhaleva, A.V. (Perm Federal Research Centre Journal, 2014)
The article discusses the influence of the Islam factor in the positioning of Russia’s regions through the prism of their representation and regional politics. Several ideal type models of the region’s positioning with the Islamic component are suggested in the article.